Factors associated with pain and osteoarthritis at the hip and knee in Great Britain's Olympians: a cross sectional study - Cooper, Dale J.; Scammell, Brigitte E.; Batt, Mark E.; Palmer, Debbie (BMJ Publishing Group, 2018)
Background: Knowledge of the epidemiology and potentially modifiable factors associated with musculoskeletal disease is an important first step in injury prevention among elite athletes.